Extinction risk of narrowly distributed species of seed plants in Brazil due to habitat loss and climate change - Silva,José Maria Cardoso da; Rapini,Alessandro; Barbosa,Luis Cláudio F.; Torres,Roger R. (PeerJ, 2019)
In a world where changes in land cover and climate happen faster than ever due to the expansion of human activities, narrowly distributed species are predicted to be the first to go extinct. Studies projecting species extinction in tropical regions consider either habitat loss or climate change as drivers of biodiversity loss but rarely evaluate them together. Here, the contribution of these two factors to the extinction risk of narrowly distributed species (with ranges smaller than 10,000 km2) of seed plants endemic to a fifth-order watershed in Brazil (microendemics) is assessed. We estimated the Regional Climate Change Index (RCCI) of these watersheds (areas with microendemics) and projected three scenarios of land use up to the year 2100 based on the average annual rates of habitat loss in these watersheds from 2000 to 2014. These scenarios correspond to immediate conservation action (scenario 1), long-term conservation action (scenario 2), and no conservation action (scenario 3). In each scenario, areas with microendemics were classified into four classes: (1) areas with low risk, (2) areas threatened by habitat loss, (3) areas threatened by climate change, and (4) areas threatened by climate change and habitat loss. We found 2,354 microendemic species of seed plants in 776 areas that altogether cover 17.5% of Brazil. Almost 70% (1,597) of these species are projected to be under high extinction risk by the end of the century due to habitat loss, climate change, or both, assuming that these areas will not lose habitat in the future due to land use. However, if habitat loss in these areas continues at the prevailing annual rates, the number of threatened species is projected to increase to more than 85% (2,054). The importance of climate change and habitat loss as drivers of species extinction varies across phytogeographic domains, and this variation requires the adoption of retrospective and prospective conservation strategies that are context specific. We suggest that tropical countries, such as Brazil, should integrate biodiversity conservation and climate change policies (both mitigation and adaptation) to achieve win-win social and environmental gains while halting species extinction.
Keywords: Biodiversity; Endemism; Biogeography; Conservation; Neotropical region; Plants; Adaptation; Policies; Global change